A case study of newly tunnels over-crossing the existing subway tunnels. (March 2022) - Wu, Ben; Liu, Wei; Shi, Peixin; Xu, Xiangyang; Liu, Yingjing
Due to the continuous expansion of congested urban areas, many new tunnels are inevitable to over-cross the existing subway lines and may even affect the operation of existing lines. It is vital to investigate the response of existing tunnel caused by over-crossing tunneling. In this study, a case history of closely spaced twin tunnels excavated above the existing tunnels in soft soil stratum was presented. The deformation of the existing tunnels induced by the excavation of the new tunnels was automatically monitored. In-situ monitoring results showed that the vertical displacement of the existing tunnels was mainly uplift and its development showed obvious phase characteristics. The increase rate of the vertical displacement in Phase I and II induced by the second over-crossing was smaller than that of the first over-crossing. A superposition method was employed to describe the uplift section characteristics of the existing tunnels. The influence ranges of tunnel excavation on the left and right lines of the existing tunnels were approximately 5.5D and 4.5D, respectively. The torsional deformation of the rail bed and the convergence of the existing tunnels are explored, and the reasons for the changes of the over-crossing sections are analyzed at the same time.